Orchestrating antigen delivery and presentation efficiency in lymph node by nanoparticle shape for immune response - Hongjuan Zhao; Yatong Li; Beibei Zhao; Cuixia Zheng; Mengya Niu; Qingling Song; Xinxin Liu; Qianhua Feng; Zhenzhong Zhang; Lei Wang (Elsevier, 2023)
Activating humoral and cellular immunity in lymph nodes (LNs) of nanoparticle-based vaccines is critical to controlling tumors. However, how the physical properties of nanovaccine carriers orchestrate antigen capture, lymphatic delivery, antigen presentation and immune response in LNs is largely unclear. Here, we manufactured gold nanoparticles (AuNPs) with the same size but different shapes (cages, rods, and stars), and loaded tumor antigen as nanovaccines to explore their disparate characters on above four areas. Results revealed that star-shaped AuNPs captured and retained more repetitive antigen epitopes. On lymphatic delivery, both rods and star-shaped nanovaccines mainly drain into the LN follicles region while cage-shaped showed stronger paracortex retention. A surprising finding is that the star-shaped nanovaccines elicited potent humoral immunity, which is mediated by CD4+ T helper cell and follicle B cell cooperation significantly preventing tumor growth in the prophylactic study. Interestingly, cage-shaped nanovaccines preferentially presented peptide-MHC I complexes to evoke robust CD8+ T cell immunity and showed the strongest therapeutic efficacy when combined with the PD-1 checkpoint inhibitor in established tumor study. These results highlight the importance of nanoparticle shape on antigen delivery and presentation for immune response in LNs, and our findings support the notion that different design strategies are required for prophylactic and therapeutic vaccines.